The Development Strategy of Carrot Commodity Marketing with the SWOT Analysis Approach in Merdeka District, Karo Regency - Sitepu, Conie Nopinda Br.; Ompusunggu, Vina Maria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The price of carrots from 2014-2016 did not increase, thus reducing carrot cultivation in Karo District, especially in Merdeka District. The cause of the decline in prices, one of the causes is a wrong marketing strategy, while the marketing strategy plays an important role in achieving business success. The purpose of this study was to identify the carrot marketing strategy by conducting a SWOT analysis. The results obtained through a SWOT analysis are as follows: Strengths of Carrot Farmers always produce quality products, their own agricultural land and marketing locations are close to agricultural land, while the weaknesses of promotional Carrot Farmers are not carried out, the sales system is too long, there is no agricultural consultant, the lack of cooperation with buyers and the workforce often shifts. SO's strategy is to utilize and improve the quality of carrots so that they can be exported, increase knowledge about carrots, increase promotion. The government's WO strategy is to participate in improving the carrot sales system, maintaining a reliable workforce with adequate salaries and facilities.